PERSEPSI PENGUNJUNG TERHADAP PELAKSANAAN PERPUSTAKAAN UMUM DI KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Munkholipah, Siti; Bahar, Aswandi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is based on the state conditions of implementation of the public library in terms of User’s Perception of the implementation of Public Library in Kecamatan Bengkalis Kabupaten Bengkalis. The research problems are whether the User’s perceptions of the implementation of the public library in Kecamatan Bengkalis Kabupaten Bengkalis is quite well?. The purpose of the research was to determine the perceptions of Users to the implementation of public library in Kecamatan Bengkalis Kabupaten Bengkalis. The population in the research were 1698 people and 30 of them was taken to be examining of the questionnaire. The sample used is simple random sampling technique with 94 people (respondent) by using Slovin formula (n= ). Instrument of data collection is a questionnaire with 184 statements and after the validity item was done, the valid items are 150. The data was analizing through quantitative descriptive approach. From the calculation of the percentage of responses was obtained tahat; user’s Perception of the implementation of Public Library in Kecamatan Bengkalis Kabupaten Bengkalis was classified as very good in indicator librarian/ attitude of librasians with a percentage value (SS+S) 84,363%. This means that the implementation of the public library in Kecamatan Bengkalis Kabupaten Bengkalis is in accordance with the standard implementation of a public library so that the public perception of the implementation of the public library in Kecamatan Bengkalis Kabupaten Bengkalis is in excellent condition.Keywords: Perception, User’s, Implementation of the Public Library.